Bionic 3D printing degradable magnesium alloy interbody fusion cage and preparation method thereof

Magnesium-strontium alloy intervertebral fusion device prepared through bionic 3D printing technology solves the problems of excessive rigidity and non-degradability of existing materials, achieves the improvement of biocompatibility and mechanical properties, promotes bone fusion and reduces concurrency The risk of symptoms has significantly improved the clinical effect.

CN119236165APending Publication Date: 2025-01-03WEST CHINA HOSPITAL SICHUAN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411181032.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing intervertebral fusion device materials have problems with excessive rigidity, non-degradability and bioindifference, resulting in unsatisfactory fusion effect, increased long-term complications, and insufficient design structure strength.

Method used

Bionic 3D printing technology is used to prepare a degradable magnesium-strontium alloy intervertebral fusion device, designed as a porous frame and through-hole mesh structure, which is completely matched with the dome structure of the intervertebral space and combines strontium elements to enhance corrosion resistance and promote bone fusion.

Benefits of technology

It achieves excellent performance of biocompatibility and mechanical properties, reduces stress occlusion effect, promotes bone tissue growth and fusion, avoids long-term complications of traditional materials, and improves early bone fusion rate and clinical application safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236165A_ABST
    Figure CN119236165A_ABST
Patent Text Reader

Abstract

The invention provides a bionic 3D printing degradable magnesium alloy interbody fusion cage and a preparation method thereof, the bionic 3D printing degradable magnesium alloy interbody fusion cage comprises a porous frame and a through hole net rack, the porous frame is constructed by supporting rods with the diameter of about 0.4 mm, the porous frame is of a compact rhombic hole structure, the aperture is about 200-400 microns, the pore coverage rate is about 50%-80%, and a horseshoe-shaped columnar space is defined; the through-hole net rack is formed by building supporting rods with the diameter of 0.2-0.1 mm, the hole diameter is about 300-800 microns, the hole coverage rate is about 90%, a dome structure is formed in the center, and the through-hole net rack is arranged in the middle of the porous frame. The magnesium-strontium alloy is adopted as a base material of the interbody fusion cage, the interbody fusion cage is integrally formed through the 3D printing technology, and the degradable characteristic and good biocompatibility of the magnesium alloy are fully utilized. The elasticity modulus of the magnesium alloy is closer to that of the human bone tissue, physiological loads can be better shared and transmitted, the stress shielding effect is reduced, and growth and fusion of the bone tissue are promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of intervertebral fusion devices, and in particular to a bionic 3D printed degradable magnesium alloy intervertebral fusion device and a preparation method thereof. Background Art

[0002] 1. Anterior cervical discectomy and fusion (ACDF)

[0003] Anterior cervical discectomy and fusion (ACDF) is one of the most classic surgical procedures for the treatment of cervical degenerative diseases and cervical trauma. This procedure is performed through an anterior approach to remove the diseased intervertebral disc and possible osteophytes, thereby relieving the compression of the nerve roots and spinal cord. At the same time, an intervertebral fusion device is implanted to maintain the intervertebral height and stability and promote intervertebral fusion. This surgical method has been widely used in clinical practice and has proven its effectiveness and safety. However, with the advancement of technology and in-depth research on biomaterials, there are still some problems that need to be solved in the existing intervertebral fusion device materials and designs.

[0004] 2. Existing intervertebral fusion materials and their problems

[0005] At present, the intervertebral fusion materials commonly used in clinical practice mainly include two categories: traditional non-degradable metal materials and polymer materials.

[0006] 2.1 Traditional non-degradable metal materials

[0007] This type of material mainly includes titanium alloy and tantalum. They have good mechanical support and strength, and can maintain the normal height of the intervertebral disc after early surgery. However, these metal materials also have some obvious disadvantages:

[0008] Excessive rigidity: Traditional metal materials are too rigid and do not match the elastic modulus of human bone tissue. This rigidity difference may cause the fusion cage to sink, resulting in loss of intervertebral height and affecting the surgical effect.

[0009] Long-term risks: Metal materials cannot be degraded in the body, and long-term presence may lead to complications such as loosening and fracture of implants such as anterior plates and screws. In addition, long-term presence of metal materials in the body may also cause chronic inflammatory reactions in tissues and other potential risks.

[0010] 2.2 Polymer Materials

[0011] Polymer materials include nano-hydroxyapatite / polyamide, polyetheretherketone (PEEK), etc. They have good biocompatibility and can be used as ideal implants. However, these materials also have some shortcomings:

[0012] Biological inertness: Although polymer materials have good biocompatibility, their biological inertness limits the ingrowth and fusion of bone tissue. This means that the effect of early bone fusion after surgery may not be ideal, affecting the long-term efficacy.

[0013] High subsidence rate: The mechanical strength of polymer materials is relatively low, and the fusion cage is prone to subsidence, resulting in loss of intervertebral height.

[0014] Non-degradable properties: Polymer materials are non-degradable in the body, which leads to a higher incidence of fusion device-related complications during long-term follow-up after surgery.

[0015] 3. Potential of magnesium alloy as intervertebral fusion material

[0016] In recent years, magnesium alloys have become a hot topic in the research of orthopedic biodegradable implants due to their unique biodegradable properties, excellent mechanical properties and biocompatibility. Magnesium is a biologically essential element with good biocompatibility. It gradually degrades in the body and can synchronize with the formation of new bone tissue, avoiding the complications caused by the long-term presence of traditional metal materials. In addition, magnesium alloys also have the following advantages:

[0017] Excellent mechanical properties: The elastic modulus of magnesium alloy is closer to that of human bone tissue, which can better share and transmit physiological loads, reduce stress shielding effects, and promote the growth and fusion of bone tissue.

[0018] Biodegradability: Magnesium alloys can gradually degrade in the body and be replaced by new bone tissue over time. They will not exist in the body for a long time, reducing the risk of long-term complications.

[0019] With the development of metallurgical technology, various improved magnesium alloys such as magnesium-calcium, magnesium-silicon, and magnesium-zinc alloys have emerged. These alloys perform better in mechanical properties and corrosion resistance, further enhancing their potential as bioimplant materials.

[0020] 4. Introduction of strontium and its role

[0021] As an important component of anti-osteoporosis drugs, strontium (Sr) has received extensive attention in orthopedic implant research in recent years. Strontium has the dual effects of inhibiting osteoclast activity and promoting osteoblast proliferation, which helps the formation and repair of bone tissue. Therefore, the introduction of strontium into magnesium alloys can not only enhance the corrosion resistance of the alloy, but also promote the growth and fusion of bone tissue and accelerate the biological integration of intervertebral fusion devices.

[0022] 5. Deficiencies of existing technologies

[0023] There are still some shortcomings in the existing intervertebral fusion cage design and material selection:

[0024] Structural strength is affected: For example, in the patent with publication number CN116687629A, the magnesium-based porous intervertebral fusion cage with bone grafting window, its larger bone grafting window and gradient pore size distribution may affect the overall structural strength of the fusion cage.

[0025] Biologically inert design: Although the porous flat metal intervertebral fusion device without bone grafting window, published as CN117582321A, is designed without bone grafting window, the biological inertness and non-bionic design of the flat metal may lead to low long-term intervertebral fusion rate and increased related complications.

[0026] In view of the above problems, the present invention provides a bionic 3D printed degradable magnesium-strontium alloy non-bone graft window-type porous intervertebral fusion device that fully matches the intervertebral dome structure. Its personalized bionic structural design allows the surface of the fusion device to fit perfectly with the intervertebral space, promotes intervertebral fusion, and avoids the mechanical strength problem in traditional designs. At the same time, the introduction of strontium elements not only enhances the corrosion resistance of the material, but also accelerates the bone fusion process, improving the clinical application effect. Summary of the invention

[0027] The purpose of the present invention is to provide a bionic 3D printed degradable magnesium alloy intervertebral fusion cage and a preparation method thereof, so as to solve the problems raised by the above-mentioned background technology.

[0028] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: a bionic 3D printed degradable magnesium alloy intervertebral fusion device, comprising a porous frame and a through-hole grid, the porous frame being constructed by support rods with a diameter of about 0.4 mm, presenting a dense diamond pore structure, a pore diameter of about 200-400 um, a pore coverage of about 50%-80%, and enclosing a horseshoe-shaped columnar space; the through-hole grid being constructed by support rods with a diameter of 0.2-0.1 mm, a pore diameter of about 300-800 um, a pore coverage of about 90%, forming a dome structure in the center, and the through-hole grid being arranged in the middle of the porous frame.

[0029] As a preferred technical solution of the present invention: the porous framework structural units are of the same size, and are horseshoe-shaped when viewed from above, and are trapezoidal structures that are narrow in front and wide in the back when viewed from the side, and can completely match the intervertebral space.

[0030] As a preferred technical solution of the present invention: the porosity of the porous frame is 50%-80%, and the porosity of the through-hole grid is 90%.

[0031] As a preferred technical solution of the present invention: the through-hole grid structure is higher than the porous frame, and the upper surface forms a dome-like structure, which completely matches the lower end plate surface of the upper vertebral body of the fusion segment.

[0032] As a preferred technical solution of the present invention: the magnesium alloy contains strontium element, and the mass fraction of strontium element is in the range of 1%-2%wt.

[0033] As a preferred technical solution of the present invention: the magnesium alloy includes one or more elements of aluminum, zinc, silicon and calcium in addition to magnesium and strontium.

[0034] As a preferred technical solution of the present invention: the porous framework is composed of a rhombic dodecahedron pore structure, and the through-hole grid is composed of a rhombic dodecahedron pore structure.

[0035] As a preferred technical solution of the present invention: the entire fusion device is integrally formed by 3D printing technology to ensure the integrity and mechanical strength of the structure.

[0036] As a preferred technical solution of the present invention: the aperture of the central layer of the through-hole grid of the fusion device is relatively small, and gradually increases from the middle to the periphery, ranging from 300-800um.

[0037] The present invention also proposes a method for preparing a biomimetic 3D printed degradable magnesium alloy intervertebral fusion cage, comprising the following steps:

[0038] a) Raw material preparation: select magnesium and strontium alloy powder, in which the mass fraction of strontium element accounts for 1%-2%wt;

[0039] b) Mixing uniformly: mixing magnesium and strontium alloy powders uniformly;

[0040] c) 3D printing: Using 3D printing technology, the uniformly mixed magnesium-strontium alloy powder is printed and formed according to the design drawings, including a porous frame and a through-hole grid. The porous frame is built by support rods with a diameter of about 0.4 mm, and the through-hole grid is built by support rods with a diameter of 0.2-0.1 mm;

[0041] d) Post-processing: Heat treatment and surface treatment are performed on the printed intervertebral fusion device to improve its mechanical properties and corrosion resistance.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] 1. Excellent biocompatibility and mechanical properties

[0044] The present invention uses magnesium-strontium alloy as the base material of the intervertebral fusion device, which is integrally formed through 3D printing technology, making full use of the degradable characteristics and good biocompatibility of magnesium alloy. The elastic modulus of magnesium alloy is closer to that of human bone tissue, which can better share and transmit physiological loads, reduce stress shielding effects, and promote the growth and fusion of bone tissue. At the same time, the introduction of strontium not only improves the corrosion resistance of magnesium alloy, but also has the dual effects of promoting osteogenesis and inhibiting osteoclastogenesis, accelerating the growth and repair of bone tissue.

[0045] 2. Bionic design and non-bone graft window structure

[0046] The intervertebral fusion device of the present invention adopts a personalized bionic design, and its porous frame and through-hole grid structure completely match the dome-like structure of the intervertebral space, so that the surface of the fusion device fits perfectly with the intervertebral space, promoting intervertebral fusion. The design without bone grafting window avoids the structural strength problem of the traditional design with bone grafting window without affecting the mechanical strength of the fusion device. At the same time, there is no need to implant additional autologous bone or allogeneic bone, reducing surgical risks and costs. The porous frame and through-hole grid structure of the fusion device give it good mechanical support and the ability to promote bone ingrowth, effectively improving the early bone fusion rate.

[0047] 3. Balance between degradation and fusion

[0048] By strictly controlling the composition ratio of magnesium-strontium alloy and the 3D printing process, the intervertebral fusion device of the present invention gradually degrades in the body, keeping pace with the formation of new bone tissue. The fusion device is gradually replaced by new bone tissue in the body, avoiding the complications caused by the long-term presence of traditional metal materials. The experimental results show that the fusion device of the present invention exhibits good biocompatibility and mechanical properties in animal experiments. While maintaining the intervertebral height, it effectively promotes the growth of new bone tissue and intervertebral fusion, verifying its safety and effectiveness in clinical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is a schematic diagram of the overall structure of the present invention;

[0050] Figure 2 This is a goat three months after ACDF surgery: A: sagittal; B: axial; C: coronal; D: three-dimensional reconstruction. New bone growth can be seen in the intervertebral space of the operated segment, and the intervertebral space height has not been significantly reduced. The plate and screws have not been displaced or loosened, and the fusion device has not been visualized, which makes it easy to observe the changes in the intervertebral space.

[0051] Figure 3 This is a goat six months after ACDF surgery: A: sagittal; B: axial; C: coronal; D: three-dimensional reconstruction. The intervertebral disc space of the operated segment can be seen to be almost completely fused, the intervertebral disc height is maintained, the plate and screws are not displaced or loosened, and the fusion device is not visualized, which facilitates the observation of intervertebral disc changes.

[0052] In the figure: 1 through-hole grid; 2 porous frame. DETAILED DESCRIPTION

[0053] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] Implementation Method 1

[0055] The present invention provides a bionic 3D printed degradable magnesium alloy intervertebral fusion cage, the design and preparation method of which are as follows:

[0056] 1. Raw materials preparation:

[0057] A magnesium-strontium alloy powder is selected, wherein the mass fraction of strontium element is 1%-2%wt. The magnesium alloy powder used can be commercial AZ31 (Mg-Al-Zn), ZK60A (Mg-Zn-Zr), etc., with strontium element added thereto.

[0058] 2. Mix well:

[0059] The magnesium alloy powder and the strontium powder are mixed evenly by ball milling for 2-6 hours to ensure that the alloy components are evenly distributed.

[0060] 3.3D printing:

[0061] Using the selective laser melting (SLM) technology, the uniformly mixed magnesium-strontium alloy powder is printed and formed according to the pre-designed drawings. The humidity and oxygen content of the printing environment are strictly controlled during the printing process to prevent the magnesium alloy from oxidizing during the printing process. The fusion device consists of two parts: a porous frame and a through-hole grid:

[0062] Porous frame: It is built by support rods with a diameter of about 0.4mm, with a dense diamond-shaped pore structure, a pore diameter of about 200-400um, a pore coverage of about 50%-80%, and encloses a horseshoe-shaped columnar space.

[0063] Through-hole grid: It is constructed by support rods with a diameter of 0.2-0.1mm, with a pore size of about 300-800um, a pore coverage rate of about 90%, and no longitudinally penetrating window structure in the center, forming a dome-like structure.

[0064] 4. Post-processing:

[0065] After printing, the molded part is slowly cooled to reduce thermal stress and deformation. The printed intervertebral fusion cage is then heat treated, specifically annealed at 350℃-450℃ for 1-3 hours to improve its mechanical properties. Finally, surface treatment, including pickling and anodizing, is performed to improve the corrosion resistance of the magnesium-strontium alloy.

[0066] 5.Structural features:

[0067] Porous frame: It is a trapezoidal structure that is narrow in front and wide in the back when viewed from the side. It can completely match the intervertebral space and ensure a perfect fit with the intervertebral space after implantation.

[0068] Through-hole grid: The aperture of the central layer is relatively small, and gradually increases from the middle to the periphery, ranging from 300-800um. The upper surface forms a dome-like structure, which completely matches the lower end plate surface of the upper vertebra of the fusion segment.

[0069] 6. Assembly and use:

[0070] During the operation, the fusion cage is implanted into the intervertebral space to perfectly match the intervertebral space. Due to the design without bone grafting window, the fusion cage does not need to be implanted with autologous bone or allogeneic bone, thus avoiding the related risks and costs.

[0071] Implementation Method 2

[0072] 1. Raw materials preparation:

[0073] A magnesium-strontium alloy powder is selected, wherein the mass fraction of strontium element is 1%-2%wt. In addition to magnesium and strontium, the alloy composition also includes one or more elements of aluminum, zinc, silicon and calcium.

[0074] 2. Mix well:

[0075] The powders were mixed by ball milling for 2-6 hours to ensure uniform distribution of alloy components.

[0076] 3.3D printing:

[0077] Using the selective laser melting (SLM) technology, the uniformly mixed magnesium-strontium alloy powder is printed and formed according to the pre-designed drawings. The fusion device consists of two parts: a porous frame and a through-hole grid:

[0078] Porous frame: It is built by support rods with a diameter of about 0.4mm, with a dense diamond-shaped pore structure, a pore diameter of about 200-400um, a pore coverage of about 50%-80%, and encloses a horseshoe-shaped columnar space.

[0079] Through-hole grid: It is constructed by support rods with a diameter of 0.2-0.1mm, with a pore size of about 300-800um, a pore coverage rate of about 90%, and no longitudinally penetrating window structure in the center, forming a dome-like structure.

[0080] 4. Post-processing:

[0081] The printed intervertebral fusion cage is slowly cooled to reduce thermal stress and deformation. It is then heat treated and annealed at 350℃-450℃ for 1-3 hours to improve its mechanical properties. Finally, it is pickled and anodized to improve corrosion resistance.

[0082] 5.Structural features:

[0083] Porous frame: When viewed from the side, it is a trapezoidal structure that is narrow in front and wide in the back, perfectly matching the intervertebral space.

[0084] Through-hole grid: The aperture of the central layer is relatively small, and gradually increases from the middle to the periphery, ranging from 300-800um. The upper surface forms a dome-like structure, which completely matches the lower end plate surface of the upper vertebra of the fusion segment.

[0085] 6. Assembly and use:

[0086] During the operation, the fusion cage is implanted into the intervertebral space to perfectly match the intervertebral space. The design without bone grafting window avoids the complications related to autologous bone harvesting and the additional cost of allogeneic bone source.

[0087] Implementation Effect

[0088] The bionic 3D printed degradable magnesium alloy intervertebral fusion cage prepared by the above implementation method showed excellent biocompatibility and mechanical properties in animal experiments. In the big-eared sheep experiment, the three-dimensional CT scan results at three and six months after surgery showed that the fusion cage gradually degraded in the body, new bone tissue grew in the pores of the fusion cage, maintained a good intervertebral height, and no obvious complications were observed, verifying the effectiveness and safety of the present invention.

[0089] Finally, the intervertebral fusion device of the present invention can be used with the bone grafting technology of autologous bone or allogeneic bone, and bone tissue is implanted in the sparse diamond holes on the upper and lower surfaces. At the same time, due to the pore size structure of the grid with gradient distribution, and the structure of large diameter of the outer frame rod, small pore size and low porosity, the entire fusion device is formed in one piece, so that the fusion device is pressure-resistant as a whole and will not collapse and decompose under pressure. In addition, the bone grafting technology allows the new bone to have more contact surface with the fusion device, thereby accelerating fusion.

[0090] Experimental example:

[0091] Experimental animals: Big-eared sheep (about 1 year old, 35±5kg, female), divided into a group with implanted fusion device and served for 3 months, and a group with served for 6 months. The fusion devices used were all 3D printed one-piece non-bone graft window-type magnesium strontium alloy porous intervertebral fusion devices. Both fusion devices consisted of a peripheral frame and a central grid. The frame had an aperture of about 200-400um, a porosity of 50-80%, a rod diameter of 0.4mm, and a grid aperture of about 300-800um, a porosity of 90%, and a rod diameter of 0.2-0.1um.

[0092] The fusion device and surgical instruments were routinely sterilized, and the experimental animals were routinely anesthetized and maintained by inhalation anesthesia. The right side of the cervical spine was used to enter the intervertebral space. The target intervertebral space was expanded using the Caspar intervertebral dilator. The upper and lower end plates were processed, and the fusion device was driven into the intervertebral space to make the fusion device and the intervertebral space completely match. An anterior cervical plate of appropriate size was placed in front. After the operation, the incision was repeatedly rinsed with saline to stop bleeding and sutured layer by layer. The two groups of experimental animals took cervical 3D CT scans at three months and six months after surgery to observe the position of the fusion device and intervertebral fusion.

[0093] After the fusion device was used in the experimental animals for three months, the coronal sagittal view of the cervical spine showed good cervical curvature, new bone formation in the intervertebral space, good maintenance of intervertebral height, and the fusion device was in place and partially degraded.

[0094] After the fusion device had been in service in the experimental animals for six months, the coronal sagittal plane of the cervical spine showed that the cervical curvature was good, the height of the intervertebral space was well maintained, the new bone connected the upper and lower vertebrae, and most of the fusion device was degraded.

[0095] The experimental animals were in good condition during the experiment, without any neurological damage, indicating that the fusion device of the present invention has good osteoinductivity, can achieve osteogenesis-degradation balance, and good matching with the intervertebral space helps to maintain the intervertebral space height for a long time. The intervertebral fusion device of the present invention overcomes the traditional view that the lack of bone grafting window will cause difficulty in new bone growth, poor fusion, and that degradable materials cannot maintain normal intervertebral space height for a long time.

[0096] The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in the field. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A bionic 3D printed degradable magnesium alloy intervertebral fusion cage, characterized by: The invention comprises a porous frame (2) and a through-hole grid (1); the porous frame (2) is constructed by support rods with a diameter of about 0.4 mm, presenting a dense diamond-shaped pore structure, a pore diameter of about 200-400 μm, a pore coverage rate of about 50%-80%, and enclosing a horseshoe-shaped columnar space; the through-hole grid (1) is constructed by support rods with a diameter of 0.2-0.1 mm, a pore diameter of about 300-800 μm, a pore coverage rate of about 90%, and a dome structure formed in the center; the through-hole grid (1) is arranged in the middle of the porous frame (2).

2. The magnesium alloy intervertebral fusion cage according to claim 1, characterized in that: The structural units of the porous frame (2) are of the same size and are horseshoe-shaped when viewed from above, and are trapezoidal structures that are narrow in front and wide in the back when viewed from the side, and can completely match the intervertebral space.

3. The bionic 3D printed degradable magnesium alloy intervertebral fusion cage according to claim 1, characterized in that: The porosity of the porous frame (2) is 50%-80%, and the porosity of the through-hole grid (1) is 90%.

4. The magnesium alloy intervertebral fusion cage according to claim 1, characterized in that: The through-hole grid (1) structure is higher than the porous frame (2), and the upper surface forms a dome-like structure that completely matches the lower end plate surface of the upper vertebral body of the fusion segment.

5. The bionic 3D printed degradable magnesium alloy intervertebral fusion cage according to claim 1, characterized in that: The magnesium alloy contains strontium element, and the mass fraction of the strontium element is in the range of 1%-2%wt.

6. The bionic 3D printed degradable magnesium alloy intervertebral fusion cage according to claim 1, characterized in that: The magnesium alloy includes, in addition to magnesium and strontium, one or more elements of aluminum, zinc, silicon and calcium.

7. The bionic 3D printed degradable magnesium alloy intervertebral fusion cage according to claim 1, characterized in that: The porous framework (2) is composed of a rhombic dodecahedron pore structure, and the through-hole grid (1) is composed of a rhombic dodecahedron pore structure.

8. The bionic 3D printed degradable magnesium alloy intervertebral fusion cage according to claim 1, characterized in that: The entire fusion device is formed in one piece using 3D printing technology to ensure the integrity and mechanical strength of the structure.

9. The bionic 3D printed degradable magnesium alloy intervertebral fusion cage according to claim 1, characterized in that: The aperture of the through-hole grid (1) of the fusion device is relatively small in the central layer, and gradually increases from the middle to the periphery, with a range of 300-800um.

10. A method for preparing the biomimetic 3D printed degradable magnesium alloy intervertebral fusion cage according to any one of claims 1 to 9, characterized in that: The following steps are involved: a) Raw material preparation: select magnesium and strontium alloy powder, in which the mass fraction of strontium element accounts for 1%-2%wt; b) Mixing uniformly: mixing the magnesium and strontium alloy powders uniformly; c) 3D printing: using 3D printing technology, a uniformly mixed magnesium-strontium alloy powder is printed and formed according to the design drawings, including a porous frame (2) and a through-hole grid (1), wherein the porous frame (2) is constructed by support rods with a diameter of about 0.4 mm, and the through-hole grid (1) is constructed by support rods with a diameter of 0.2-0.1 mm; d) Post-processing: Heat treatment and surface treatment are performed on the printed intervertebral fusion device to improve its mechanical properties and corrosion resistance.

Citation Information

Cited By

  • Preparation method and device of structure and function integrated bionic interbody fusion cage

    CN121081171A